Towards A Bully-Free Pesantren: The Role of Educational Management With Adaptive Psychology and Mental Health Interventions - Muhammad Anggung Manumanoso Prasetyo; Iswan Fadlin; Ruchdee Madman (At-Ta'dib, 2023)
Bullying's complexity is influenced not only by the individual's features and behavioural tendencies but also by the practice of family upbringing, as well as environmental elements such as the frequency and type of bullying. A qualitative paradigm is used in the research. The sampling method employing the purposive sampling technique seeks to identify teenagers who have been bullied. Interviews, observations, and documentation reviews of bullying episodes were used to collect data. Dayah leaders in the area of parenting serve as study informants. The veracity of the data is checked using sources of persons involved in bullying. Data triangulation techniques and peer discussion were used to examining the data. The findings revealed that verbal bullying occurred in Islamic boarding schools. Adaptive psychology is demonstrated through students' communication abilities, which are classified as passive communication, aggressive communication, and forceful communication. Meanwhile, adaptive techniques such as enhancing teacher counselling abilities (informative-communicative), monitoring assessments, and anti-bullying policies are used to provide mental health coaching. Students, on the other hand, are expected to cooperate with the facts of the occurrence under the structure of the solution-focused counselling strategy. Cultural reference, resources, research literature, formalization, and pesantren policy are all institutionally focused on in adaptive psychology. So far, the pesantren are concerned about their reputation; consequently, the societal consequences of this study need pesantren management to be upfront whenever bullying occurs.